Herstory as an Important Force in Bioethics - Sodeke, Stephen (The Hastings Center report, 2022)
This tribute celebrates the life and work of Marian Gray Secundy (1938-2002), who was the first director of the National Center for Bioethics in Research and Health Care, a passionate advocate for health equity, a visionary scholar, and a skilled editor and collaborator. Within the tribute are several short remembrances in which individuals describe their association with Secundy to honor her as a leader, friend, scholar, advocate, and teacher in bioethics.